ANALISIS PENGGUNAAN DIKSI DALAM PUISI SELAMAT PAGI INDONESIA KARYA SAPARDI DJOKO DAMONO SEBAGAI BAHAN AJAR APRESIASI SASTRA DI SMA - Pipik Asteka (Universitas Majalengka, 2017)
AbstractLanguage as a communication tool consists of two kinds, namely spoken and written languages. The scope of Indonesian subjects covers the components of language skills and literary abilities which cover four aspects of skills, namely as follows: first, listening; second speak; third, reading and fourth, writing. Literary learning tends to be less daring to explore text in a broader context. Even though it is very possible the teacher invites students to enter and explore the elements of literary builder from outside the learning text. This study aims to describe the selection of poetry for the benefit of alternative teaching materials and to improve the learning outcomes of Indonesian Language and Literature in high school. In this study the authors used a descriptive analysis method, which is a research method that aims to provide an analysis, systematic, factual and thorough phenomenon. The qualitative analysis method aims to reveal the characteristics of the possibility of Good Morning Indonesia poetry by Sapardi Djoko Damono whether or not feasible if used as teaching materials for Literary Appreciation in high school. The results of the research hypothesis can be accepted, this can be illustrated from the results of the assessment of the Good Morning Indonesian poetry by Sapardi Djoko Damono in terms of elements of diction that qualify or are suitable as teaching materials for literature appreciation in high school. The results of the research show that the elements of Good Morning Indonesia diction by Sapardi Djoko Damono Decent as a material for literature appreciation in high school can be seen from its contents which are in accordance with the characteristics, experiences and needs of high school students.Keyword: Diction, Pusisi Selamat Pagi Indonesia, Teaching Materials, Literary Appreciation AbstrakBahasa sebagai alat komunikasi terdiri atas dua ragam yaitu bahasa lisan dan bahasa tulis. Ruang lingkup mata pelajaran Bahasa Indonesia mencakup komponen kemampuan berbahasa dan kemampuan bersastra yang meliputi empat aspek keterampilan, yaitu sebagai berikut: pertama, menyimak; kedua berbicara; ketiga, membaca dan keempat, menulis. Pembelajaran sastra cenderung kurang berani menggali teks dalam konteks yang lebih luas. Padahal sangatlah mungkin guru mengajak siswa untuk masuk dan menyelami unsur pembangun sastra dari luar teks pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan pemilihan puisi untuk kepentingan alternatif bahan ajar dan peningkatan hasil pembelajaran Bahasa dan Sastra Indonesia di SMA. Dalam penelitian ini penulis menggunakan metode deskriptif analisis, yaitu metode penelitian yang bertujuan untuk memberikan suatu fenomena secara analisis, sistematis, faktual dan teliti. Metode analisis kualitatif bertujuan untuk mengungkapkan karakteristik kemungkinan puisi Selamat Pagi Indonesia karya Sapardi Djoko Damono layak atau tidak jika dijadikan bahan ajar Apresiasi Sastra di SMA. Hasil hipotesis penelitian dapat diterima, hal ini dapat tergambar dari hasil penilaian puisi Selamat Pagi Indonesia karya Sapardi Djoko Damono ditinjau dari unsur diksi yang memenuhi syarat atau layak sebagai bahan ajar apresiasi sastra di SMA. Hasil penelitian menunjukkan unsur diksi Selamat Pagi Indonesia karya Sapardi Djoko Damono Layak sebagai bahan ajar apresiasi sastra di SMA terlihat dari isinya yang sesuai dengan karakteristik, pengalaman dan kebutuhan siswa SMA.Kata Kunci: Diksi, Puisi Selamat Pagi Indonesia, Bahan Ajar, Apresiasi Sastra